Low FNDC5/Irisin expression is associated with aggressive phenotypes in gastric cancer - Xu, Luyun; Ye, Yan; Sun, Yuqin; Zhong, Wenting; Chi, Liangjie; Lin, Youyu; Liu, Hongxia; Li, ShengZhao; Chen, Hui; Li, Chengcheng; Lin, Yuxuan; Wang, Qingshui; et al. (Frontiers in Pharmacology, 2022)
Background： FNDC5 (fibronectin type III domain containing 5) belongs to the family of proteins called fibronectin type III domain-containing which carry out a variety of functions. Irisin, a newly discovered exercise-induced cytokine produced by the proteolytic hydrolysis of FNDC5, has been shown to affect the proliferation of some cancer cells and chemosensitivity of anticancer drugs like doxorubicin (DOX). The expression of FNDC5 has been found to be associated with the occurrence and development of tumors. However, the functions of FNDC5 in gastric cancer remain relatively unknown. Methods： The expression and prognosis of FNDC5 in gastric cancer were analyzed based on The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) database. The effects of FNDC5 on gastric cancer development and progression, function in gastric cancer cells, and potential underlying mechanisms were examined. Cox univariate and LASSO analyses were used to develop risk signatures based on FNDC5-related genes, and the prognostic model was validated. Then, a Nomogram model is constructed for survival prediction and validation of gastric cancer patients. Results: Data from GEO and TCGA databases indicated that FNDC5 was decreased in gastric cancer tissues compared to normal gastric tissues. However, survival analysis indicated that lower FNDC5 mRNA levels were associated with better overall survival and disease-free survival in gastric cancer patients. Meanwhile, a significant negative correlation between FNDC5 and the abundance of CD4+ memory T cells in gastric cancer was found. In vitro overexpression of FNDC5 inhibits the migration and invasion of gastric cancer cells, without affecting proliferation. The analysis of transcription factor and methylation revealed that low expression of FNDC5 in gastric cancer may be related to the expression of transcription factor KLF9 and the methylation of cg00668227 locus. Finally, A two-gene risk score module based on FNDC5 co-expressed gene was built to predict the overall clinical ending of patients.